Human responsibility for nature in the perspective of the ecological crisis - Kuzior, Aleksandra (Studia Ecologiae et Bioethicae, 2007)
The article takes up the issues connected to the ecological crisis, causes of which refer to uncontrolled scientifically-technical development, predatory administration of the natural sources of Earth and disrespect of the nature, following from the anthropocentric axiology, the analysis of the Stockholm’s Declaration, the Declaration from Rio and the declaration from Johannesburg, as documents forming the idea of the sustainable development, active that care and respect of nature and preventing degratation of natural environment make a basis of the agricultural and social development and the only rational way to get out of the ecological crisis without radical reduction the quality of human’s life. In discussed declarations they point out the individual, collective and institutional responsibility. It’s set up that the basis of the responsibility figured out like that - for the other human, for present and future generations, for the nature, for the global human’s society, for other communities of alive creatures, for the planet - should be ecophilosophy and systematic sozology. Basing on this two sciences we can make a socio-economical and ecological order indicated in the sustainable development conception.